2017
DOI: 10.1536/ihj.16-289
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Extracorporeal Shock Wave Myocardial Revascularization Therapy for Post-Acute Myocardial Infarction Patients and Refractory Angina Pectoris Patients

Abstract: Extracorporeal shockwave myocardial revascularization (ESMR) is one of the new treatment options for refractory angina pectoris (RAP), and some studies have indicated its effectiveness. A single-arm prospective trial to assess the feasibility of ESMR using Cardiospec for patients with post-acute myocardial infarction (AMI) and RAP was designed and performed. The patients were treated with 9 sessions of ESMR to the ischemic areas for 9 weeks. The feasibility measures included echocardiography; cardiac magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Early thrombolytic therapy or percutaneous coronary intervention has been adopted to recover blood perfusion in the ischemic site. This method effectively rescues the injured myocardium ( 1 ) and improves myocardial ischemia and necrosis ( 2 ). However, adverse effects include partial myocardial cell apoptosis and loss of heart function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early thrombolytic therapy or percutaneous coronary intervention has been adopted to recover blood perfusion in the ischemic site. This method effectively rescues the injured myocardium ( 1 ) and improves myocardial ischemia and necrosis ( 2 ). However, adverse effects include partial myocardial cell apoptosis and loss of heart function.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, acute myocardial infarction (AMI) is a factor that primarily results in increasing morbidity of CVD patients ( 1 ). Therefore, early, timely and accurate diagnosis and evaluation of AMI are essential for actively administrating effective treatment ( 2 ). Furthermore, early diagnosis may result in timely cardiac reperfusion and reduce mortality ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Research works demonstrated that activation of Wnt/β-catenin signaling enhances myogenesis, 10 increases myoblast proliferation, and enhances muscle growth, 11,12 whereas, it has been reported that Wnt/β-catenin signaling can be activated by mechanotransduction. 13,14 Low-intensity extracorporeal shockwave therapy (Li-ESWT) is one example of a mechanical force that has been employed for many years to treat musculoskeletal disorders, 15 ischemic heart disease, 16,17 and vasculogenic ED. 18,19 We previously reported that Li-ESWT activated penile stem cells 20,21 and very recently, we have applied Li-ESWT effectively to improve SUI.…”
Section: Introductionmentioning
confidence: 99%
“…12) Moreover, the impaired left ventricular systolic function would not fully recover even after surgical or catheter interventions. 13,14) On the other hand, the impaired left ventricular systolic function in Takotsubo cardiomyopathy would fully recover without surgical or catheter interventions in a few weeks. 1) In fact, the cardiac scintigraphy results clearly revealed recovery of the left ventricular systolic function in the present case.…”
Section: Discussionmentioning
confidence: 99%